Be ethical in critical times: An option or an obligation? / Naziatul Aziah Mohd Radzi, Normaizatul Akma Saidi and Ahmad Fahme Mohd Ali - Mohd Radzi, Naziatul Aziah; Saidi, Normaizatul Akma; Mohd Ali, Ahmad Fahme (2021)
The Covid-19 pandemic has caused chaos around the globe. This extraordinary pandemic is considered a major disaster, where millions of lives have been lost and many more have suffered because of the pandemic’s chain effect. To control the spread of the virus, various measures are taken and imposed; for some countries, movement restrictions or lockdowns have been enforced. The implementation of movement restrictions has contributed various implications to all layers of society. Nonetheless, movement restriction, along with selfquarantine, is the best and most effective method of curbing the transmission of Covid-19. In 2020, Malaysia implemented the Movement Control Order and managed to reduce the number of daily cases to a single digit, which even recorded 0 cases at certain points. However, the sky is not always clear, as daily cases of infection have been increasing since the end of 2020. The gradual increase in the number of daily cases has pushed the local health care to the maximum capacity, as cases climbed from hundreds to thousands. As a result, the government has been compelled to announce Movement Control Order 3.0 to control and reduce the number of infections. Nevertheless, this article does not intend to point fingers or find the root cause to the sharp increase in the number of cases; instead, this article will discuss the ethical elements that need to be demonstrated by all parties when facing a critical situation like the present. According to the Dewan Bahasa dan Pustaka, ethics is defined as the knowledge related to morally accepted principles that are held by an individual or a group. Ethics comprises the standards of behaviour to which we adhere, be it in our personal lives or professional settings. It is a norm for behavior that differentiates between acceptable and unacceptable behaviour and plays an important role in our living (Mikesell et al., 2013). Honesty, empathy, trustworthiness, and other virtues are part of the elements in ethics, in which we identify our expected personal behaviour and desired public reputation.